Hydrogen Sulfide Alleviates Lipopolysaccharide-Induced Diaphragm Dysfunction in Rats by Reducing Apoptosis and Inflammation through ROS/MAPK and TLR4/NF-κB Signaling Pathways. (24th May 2018) - Zhang, Guo-Yu; Lu, Dan; Duan, Shao-Feng; Gao, Ying-Ran; Liu, Shi-Yu; Hong, Ya; Dong, Peng-Zhen; Chen, Ya-Ge; Li, Tao; Wang, Da-Yong; Cheng, Xiang-Shu; He, Fei; et al.
Abstract : Diaphragm dysfunction is an important clinical problem worldwide. Hydrogen sulfide (H2 S) is involved in many physiological and pathological processes in mammals. However, the effect and mechanism of H2 S in diaphragm dysfunction have not been fully elucidated. In this study, we detected that the level of H2 S was decreased in lipopolysaccharide- (LPS-) treated L6 cells. Treatment with H2 S increased the proliferation and viability of LPS-treated L6 cells. We found that H2 S decreased reactive oxygen species- (ROS-) induced apoptosis through the mitogen-activated protein kinase (MAPK) signaling pathway in LPS-treated L6 cells. Administration of H2 S alleviated LPS-induced inflammation by mediating the toll-like receptor-4 (TLR-4)/nuclear factor-kappa B (NF- κ B) signaling pathway in L6 cells. Furthermore, H2 S improved diaphragmatic function and structure through the reduction of inflammation and apoptosis in the diaphragm of septic rats. In conclusion, these findings indicate that H2 S ameliorates LPS-induced diaphragm dysfunction in rats by reducing apoptosis and inflammation through ROS/MAPK and TLR4/NF- κ B signaling pathways. Novel slow-releasing H2 S donors can be designed and applied for the treatment of diaphragm dysfunction.